2021
DOI: 10.1002/adma.202105917
|View full text |Cite
|
Sign up to set email alerts
|

Dense Silicon Nanowire Networks Grown on a Stainless‐Steel Fiber Cloth: A Flexible and Robust Anode for Lithium‐Ion Batteries

Abstract: Silicon nanowires (Si NWs) are a promising anode material for lithium‐ion batteries (LIBs) due to their high specific capacity. Achieving adequate mass loadings for binder‐free Si NWs is restricted by low surface area, mechanically unstable and poorly conductive current collectors (CCs), as well as complicated/expensive fabrication routes. Herein, a tunable mass loading and dense Si NW growth on a conductive, flexible, fire‐resistant, and mechanically robust interwoven stainless‐steel fiber cloth (SSFC) using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 64 publications
0
38
0
Order By: Relevance
“…Moreover, tin is a lithium-alloying material that can participate in lithiation/delithiation. Several studies have demonstrated its ability to grow SiNWs [ 21 , 22 , 23 , 24 , 25 ] and the capacity of tin-grown silicon as an anode material in lithium-ion cells [ 25 ]. Growth must also allow for the control of the structure, size and shape of the SiNWs, as these features have a strong impact on their electrochemical behavior [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, tin is a lithium-alloying material that can participate in lithiation/delithiation. Several studies have demonstrated its ability to grow SiNWs [ 21 , 22 , 23 , 24 , 25 ] and the capacity of tin-grown silicon as an anode material in lithium-ion cells [ 25 ]. Growth must also allow for the control of the structure, size and shape of the SiNWs, as these features have a strong impact on their electrochemical behavior [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The content of C, N, Zn, and Si elements in the composite sample is 64. confirming that Zn element in the MDNs exists as single atoms. The XRD pattern of the Si NDs⊂MDN displays three typical diffraction peaks corresponding to the (111), (220), and (311) planes of Si crystal (JCPDS 27-1402), [37][38][39] respectively, suggesting Si nanodots are in crystalline phase. Raman spectrum of the Si NDs⊂MDN and MDN (Figure 2b) exhibits typical peaks corresponding to Si, and D and G bands of graphitic carbon, [37,38,40] respectively, in good agreement with the XRD characterization.…”
Section: Synthetic Strategy and Materials Characterizationsmentioning
confidence: 99%
“… 26 31 The seed here is a catalyst to lower the eutectic temperature and at the end of the reaction remains intact as a metal particle either coupled to the semiconductor component as a heterostructure or separated in solution. 32 34 …”
Section: Introductionmentioning
confidence: 99%